The high affinity IgE receptor Fc epsilonRI is expressed by human intestinal epithelial cells. - Eva Untersmayr; Giovanna Bises; Philipp Starkl; Charles L Bevins; Otto Scheiner; George Boltz-Nitulescu; Fritz Wrba; Erika Jensen-Jarolim (PLoS ONE)
Background IgE antibodies play a paramount role in the pathogenesis of various intestinal disorders. To gain insights in IgE-mediated pathophysiology of the gut, we investigated the expression of the high affinity IgE receptor Fc epsilonRI in human intestinal epithelium. Methodology/principal findings Fc epsilonRI alpha-chain, as detected by immunohistochemistry, was positive in epithelial cells for eight of eleven (8/11) specimens from colon cancer patients and 5/11 patients with inflammation of the enteric mucosa. The Fc epsilonRIalpha positive epithelial cells co-expressed Fc epsilonRIgamma, whereas with one exception, none of the samples was positive for the beta-chain in the epithelial layer. The functionality of Fc epsilonRI was confirmed in situ by human IgE binding. In experiments with human intestinal tumor cell lines, subconfluent Caco-2/TC7 and HCT-8 cells were found to express the alpha- and gamma-chains of Fc epsilonRI and to bind IgE, whereas confluent cells were negative for gamma-chains. Conclusions/significance Our data provide the first evidence that the components of a functional Fc epsilonRI are in vitro expressed by the human intestinal epithelial cells depending on differentiation and, more importantly, in situ in epithelia of patients with colon cancer or gastrointestinal inflammations. Thus, a contribution of Fc epsilonRI either to immunosurveillance or pathophysiology of the intestinal epithelium is suggested.